Evaluation of the Permeability of Concrete with the Addition of Glass Powder - Josias Mikhail, Castillo Prado (2025)
The article presents the usefulness of implementing the use of recycled glass powder, after having carried out the permeability test, evaluated at the age of 28 days. This with the purpose of seeking a sustainable and low-cost alternative to improve the durability of concrete exposed to humid climates compared to conventional concrete. The influence of pulverized glass shows a positive impact on the mechanical properties of the concrete at the age of 28 days, through the permeability test. In a comparative study it is shown that adding glass powder produces workable samples obtained according to the slump test. On the one hand, being in a humid climate, water infiltration was measured due to the humidity of the concrete. For this purpose, the permeability test was carried out following what is described in the American standard ASTM C107. On the other hand, it was analyzed that powdered glass can improve the properties of concrete, since it has a positive contribution to the properties analyzed and achieving a waterproof concrete with a dosage of VP05. This brings benefits in the construction sector not only in improving the properties of concrete, but also in making more sustainable concretes.